Risco de câncer de pele em indivíduos com menos de quarenta anos de idade em Goiânia - Pereira, Samir (2013)
Background Skin cancer is the most common malignant neoplasm affecting Caucasian population worldwide. Its incidence has increased globally in the last decades. There are few existing incidence studies focusing on individuals under the age of 40. Objectives Verify incidence and trends for non-melanoma skin cancer as well as for multiple skin malignant neoplasms in populations under the age of 40 in Goiânia, Central-west Brazil, 1988-2009. Methodology A descriptive epidemiological study is reported herein on melanoma skin cancer (MSC) and on non-melanoma skin cancer (NMSC). Incident cases were obtained from the Population-Based Cancer Registry (PBCR) of Goiânia and from its sources. Incident cases with single- or multiple-lesions were identified. The existence of genetic syndromes and/or transplants (in the cases of multiple lesions) was investigated. Frequency, incidence and trends were analyzed for NMSC as well as for single- and multiple- lesion cases. Results: From 1988 to 2009, 1995 skin cancer were identified in 1688 pacients, of which 1614 were basal cell carcinoma (BCC), 222 were squamous cell carcinoma (SCC), and 159 MSC. Analysis revealed 1524 (90.3%) single-lesion cases and 164 (9.7%) multiple-lesion cases. Of these, 10% presented association with genetic syndromes, with an average of 5.4 lesions, while for non-associated cases the average was 2.6 lesions. BCC incidence increased from 1.70 to 3.69 in men and from 2.38 to 6.14 per 100,000 in women in the period. Significant increasing trends were verified for men with APC = 2.8% and for women with APC = 3.9%. BCC incidence trends revealed increases per age group (in men starting from the age of 30 and in women starting from the age of 25) and per topography (in head and neck and members in men, and for all anatomical regions in women). Regarding SCC, non-significant decreasing trends were verified for both genders. Conclusions: Non-melanoma skin cancer in young individuals is not rare. BCC incidence has increased in the population under the age of 40 in Goiânia, Central-west Brazil, especially among women. Approximately 10% of cases are multiple-lesion type, of which for 90% no association was established with genetic syndromes or transplants.